Comprehensive Physiology 2016
DOI: 10.1002/cphy.c150014
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Steroid Regulation of Mood and Behavior

Abstract: In this article, we examine evidence supporting the role of reproductive steroids in the regulation of mood and behavior in women and the nature of that role. In the first half of the article, we review evidence for the following: (i) the reproductive system is designed to regulate behavior; (ii) from the subcellular to cellular to circuit to behavior, reproductive steroids are powerful neuroregulators; (iii) affective disorders are disorders of behavioral state; and (iv) reproductive steroids affect virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 387 publications
(473 reference statements)
2
80
0
3
Order By: Relevance
“…First, a continuous exposure to hormones reminiscent of pregnancy could be an effective treatment for some women with PMDD (41). Studies using oral contraceptives have confirmed their efficacy in some women with PMDD (4247).…”
Section: Discussionmentioning
confidence: 99%
“…First, a continuous exposure to hormones reminiscent of pregnancy could be an effective treatment for some women with PMDD (41). Studies using oral contraceptives have confirmed their efficacy in some women with PMDD (4247).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] As underlying mechanism contributing to this continuous health decline, age-related changes in steroid secretion have been suggested. 4,5 In aging men testosterone (T), the end product of the hypothalamus-pituitary-gonadal (HPG)…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…SNRI ("selective noradrenaline reuptake inhibitors") kann eine effektive Ovulationshemmung durch hormonale Kontrazeptiva vorgenommen werden. Im Vergleich zur zyklischen Gabe hat sich der Langzyklus als signifikant wirksamer erwiesen [47,48].…”
Section: Prämenstruelles Syndromunclassified